1983
DOI: 10.1037/0022-006x.51.4.504
|View full text |Cite
|
Sign up to set email alerts
|

Hopelessness, depression, and suicidal intent among psychiatrically disturbed inpatient children.

Abstract: The present investigation evaluated hopelessness, depression, and suicidal intent among children (8 to 13 years old) hospitalized on a psychiatric intensive care service. A hopelessness scale, modeled after the adult version, was developed and administered to 66 children along with measures of depression (Children's Depression Inventory, Bellevue Index of Depression, Depression Symptom Checklist) and self-esteem (Self-Esteem Inventory). As predicted, children who scored high on the hopelessness scale showed si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
219
5
3

Year Published

1985
1985
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 431 publications
(240 citation statements)
references
References 11 publications
13
219
5
3
Order By: Relevance
“…These results parallel those found with adults and are also consistent with a number of studies on depression-related cognitions in children. Kazdin, French, Unis, Esveldt-Dawson, and Sherick (1983) demonstrated That a children's version of Beck's Hopelessness scale was significantly related to severity of depression on the CDI and to suicidal intent among psychiatric inpatient children . With non-clinical children, Moyal ( 1977) reported that a self-blaming tendency and an external locus of control were correlated with depression , whereas Seligman et al ( 1984) found that internal attributions for negative events were correlated with the CDI.…”
Section: Discussionmentioning
confidence: 99%
“…These results parallel those found with adults and are also consistent with a number of studies on depression-related cognitions in children. Kazdin, French, Unis, Esveldt-Dawson, and Sherick (1983) demonstrated That a children's version of Beck's Hopelessness scale was significantly related to severity of depression on the CDI and to suicidal intent among psychiatric inpatient children . With non-clinical children, Moyal ( 1977) reported that a self-blaming tendency and an external locus of control were correlated with depression , whereas Seligman et al ( 1984) found that internal attributions for negative events were correlated with the CDI.…”
Section: Discussionmentioning
confidence: 99%
“…The 27-item CDI has high internal consistency and moderate retest reliability, and it correlates with measures of related constructs (Kazdin, French, Unis, Esveldt-Dawson, & Sherick, 1983).…”
Section: Methodsmentioning
confidence: 99%
“…The Hopelessness Scale for Children is a 17-item, self-report, true-false scale designed to measure the continuum of hope to hopelessness [31]. The child is asked to agree or disagree with statements such as, "I want to grow up because I think things will get better."…”
Section: Participantsmentioning
confidence: 99%